Development and Acceptability of Virtual Laboratory in Learning Systematics - Sison, Arnolfo Jade Ryan N.; Bautista, Jason M.; Javier, Janine L.; Delmonte, Renee Juselle B.; Cudera, Rizalyn B. (ASEAN Journal of Educational Research and Technology, 2024)
Virtual laboratory increases learning engagement and may be illustrated through the use of technology and animation media, making it simpler for students to learn and acquire knowledge. This study aimed to develop a Virtual Laboratory In Learning Systematics (ViLIS) website utilizing the Analysis, Design, Development, and Evaluation (ADDE) that would provide users with an array of different interactive activities in various concepts covered in the subject biology in the topic systematics specifically on insects, and provide additional instructional material for teachers. This quantitative study also determined the acceptability level of the developed virtual website. The level of acceptability of the developed virtual laboratory was evaluated by science students and teachers/IT experts based on content, technical, and instructional qualities. The overall results showed that ViLIS satisfied the quality components with an interpretation of “Very High Quality”. It is recommended to conduct an intervention to strengthen the feasibility and effectiveness of the created virtual laboratory.